Plasminogen activator inhibitor-1 is elevated, but not essential, in the development of bleomycin-induced murine scleroderma - Matsushita, M (Blackwell Science Inc, 2005)
Accumulative data have demonstrated that plasminogen activator inhibitor-1 (PAI-1) plays an important role in the extracellular matrix metabolism; however, the involvement of PAI-1 in scleroderma has not been fully elucidated. In this study, we investigated the role of PAI-1 in bleomycin-induced murine scleroderma. 100 µg of bleomycin was injected subcutaneously to the back skin of C3H/HeJ mice on alternate day for 4 weeks. Histopathological findings revealed that PAI-1 was positive in macrophage-like cells and fibroblastic cells in the dermis, in parallel with the induction of dermal sclerosis. PAI-1 mRNA expression in the whole skin was up-regulated at 1 and 4 weeks. The production of active PAI-1 protein in the lesional skin was significantly increased 3 and 4 weeks after bleomycin treatment. Next, we examined whether dermal sclerosis is induced by bleomycin in PAI-1-deficient (PAI-1–/–) mice. 10 µg of bleomycin was subcutaneously injected to PAI-1–/– and wild type (WT) mice 5 days per week for 4 weeks. Histological examination revealed that dermal sclerosis was similarly induced even in PAI-1–/– as well as WT mice. Dermal thickness and collagen contents in the skin were significantly increased by bleomycin injection in both PAI-1–/– and WT mice, and the rate of increase was similar. These data suggest that PAI-1 plays an important role, possibly via TGF-β pathway activation. However, the fact that PAI-1 deficiency did not ameliorate skin sclerosis suggest that PAI-1 is not the essential factor in the development of bleomycin-induced scleroderma, and more complex biochemical effects other than PA/plasmin system are greatly suspected.